Computational Investigation for Secondary Structure Prediction - , G.Nageswara Rao, M.Rithvik (International Journal of Scientific Research and Management (IJSRM), 2014)
: Protein structure prediction play a key role in every living organisms All living organisms are made up of cells andeach cell in its turn consists of certain protein consequences which exercise an important role in catalyzing the chemicalreactions. So, a study of a protein structure becomes a search lamp in the diagnosis of a disease .when the percent identitybetween two protein sequences falls below 33%,it necessities to carry out the analysis of protein secondary structure. Of theseveral methodologies developed to analyze the protein secondary structure, two methods proved to be soundDSSP(Dictionaryof Secondary Structure of Proteins) and GOR(Garnier,Osguthrope and Robson),Even though the predictionaccuracy of GORV is 73.5% due to hazards in its implementation ,GORIV is generally used in spite of its accuracy being onlyto 64.4%